1990
DOI: 10.1096/fasebj.4.5.2407590
|View full text |Cite
|
Sign up to set email alerts
|

Movement of proteins through the Golgi stack: a molecular dissection of vesicular transport 1

Abstract: A combination of cell-free biochemical and morphological studies has revealed that a coated bud-coated vesicle transport system shuttles newly synthesized proteins through the successive processing compartments of the Golgi apparatus. These Golgi-coated vesicles operate in a manner formally analogous to the clathrin-coated, pit-coated vesicle system responsible for receptor-mediated endocytosis; however Golgi-coated vesicles do not contain clathrin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(74 citation statements)
references
References 0 publications
3
71
0
Order By: Relevance
“…Bar, 10 um. inhibited in the presence of GTPyS (28,31,36) and, in turn, the effect of BFA on ß-COP is blocked by GTPyS or aluminium fluoride (10) . Preliminary studies have shown that the dissociation of p200 from the Golgi in the presence of BFA is also blocked by GTPyS and aluminium fluoride, suggesting a role for G proteins in its membrane association (J .…”
Section: Discussionmentioning
confidence: 99%
“…Bar, 10 um. inhibited in the presence of GTPyS (28,31,36) and, in turn, the effect of BFA on ß-COP is blocked by GTPyS or aluminium fluoride (10) . Preliminary studies have shown that the dissociation of p200 from the Golgi in the presence of BFA is also blocked by GTPyS and aluminium fluoride, suggesting a role for G proteins in its membrane association (J .…”
Section: Discussionmentioning
confidence: 99%
“…This commonality has led to the isolation and cloning of NEM-sensitive factor (Rothman and Orci, 1990), a cytosolic factor that is required for membrane-membrane fusion between vesicles in these membrane transportpathways. SinceNEM treatment ofcytosol did not affect coated pit budding in vitro, apparently this factor is not required.…”
Section: Discussion Purified Plasma Membranes Support Coated Pit Buddingmentioning
confidence: 99%
“…If removal of ARFs uncouples fusion from budding and leads to direct fusion of donor and acceptor membranes, then the lag in glycosylation-coupled transport thought to reflect the time required to form vesicles on the donor Golgi membranes (Balch et al, 1984b;Rothman and Orci, 1990) should disappear. Assays containing saturating concentrations of cytosol were incubated for various intervals at 30°C and then transferred to ice to arrest further transport (Balch et al, 1984a Figure 4A), the relative kinetics of transport in Figure 6.…”
Section: Removal Of Arfs From Transport Assays Has No Effect On the Rmentioning
confidence: 99%